Adverse Events and Complications in Continuous Intra-arterial Nimodipine Infusion Therapy After Aneurysmal Subarachnoid Hemorrhage - Kapapa, Thomas; König, Ralph; Mayer, Benjamin; Braun, Michael; Schmitz, Bernd; Müller, Silwia; Schick, Julia; Wirtz, Christian Rainer; Pala, Andrej (Frontiers in Neurology, 2022)
Objective To determine the frequency and severity of complications associated with the continuous intra-arterial infusion of nimodipine (CIANI) as a new treatment of delayed cerebral ischemia (DCI) after aneurysmal subarachnoid hemorrhage (SAH). Methods Patients from two centers (n = 718) treated for SAH between 2008 and 2016 were included. Demographic and SAH-related parameters were evaluated, and also the frequency of adverse events (AEs) and complications including their severity (mild, moderate, and severe). Clinical outcome was analyzed using Glasgow Outcome Scale (GOS). The unfavorable outcome was defined as GOS 1 to 3, and favorable outcome as GOS 4 to 5. The Short-Form 36 (SF-36) health-related quality-of-life (QoL) questionnaire served as a QoL measurement. Results Of 718 patients, 65 (9%) were treated by CIANI and had a higher clinical or imaging grade of bleeding severity. Clinical deterioration while on treatment happened more often in patients who were treated with CIANI than in others. In patients with CIANI, 67% had AEs and/or complications during the treatment. Nimodipine-associated hypotension was seen in 8% (mild). Catheter-associated thrombus occurred in 9% (moderate). New intracerebral hemorrhage was found in 14% (moderate). A total of 6% treated by CIANI died during the treatment period (severe). More than one-third (39%) of patients of CIANI reached at least moderate disability, and 23% showed good recovery. Patients who received CIANI showed reduced QoL, but differences in mental and general health, and also pain were minimal. Conclusion Patients who received CIANI had higher rates of AEs and complications. However, this does not exclude the possibility that the use of CIANI might be helpful in patients with severe and therapy-refractory CV and DCI. Controlled and randomized studies would be helpful to clarify this question but they are methodologically and ethically challenging.